Fast-charging graphite material with multi-metal doping and preparation method of fast-charging graphite material
By doping polymetallic ions into the negative electrode graphite material of lithium-ion batteries, supporting the layer spacing and improving conductivity, the poor contact and cyclic expansion of the battery during charging and discharging are solved, and the rate performance and safety of the battery are improved.
Patent Information
- Application Number
- CN202411104494.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-27
AI Technical Summary
During the charging and discharging process of existing lithium-ion battery negative graphite materials, there are problems such as poor contact between electrode material particles and current collectors, large surface resistance, poor peeling strength, and cyclic expansion, resulting in poor cycle life and stability and rapid Lithium ions are prone to deposition to form lithium dendrites during charging, which poses safety hazards.
Using a multi-metal doped fast charging graphite negative electrode material preparation method, the second metal ions (such as Ag and Au are promoted by doping a larger size first metal ion (such as vanadium) into the graphite material to support a large layer spacing. ) incorporates the conductivity and heat treatment under a reducing atmosphere to improve the embedding and precipitation efficiency of lithium ions.
It effectively improves the conductivity of the material and the embedded/precipitation performance of lithium ions, improves the rate charging performance and cycle stability, reduces the formation of lithium dendrites, and enhances the safety of the battery.
Smart Images

Figure CN119191286A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery negative electrode materials, and in particular to a fast-charging graphite negative electrode material with multi-metal doping and a preparation method thereof. Background Art
[0002] Carbon materials have the advantages of high lithium storage capacity, abundant raw materials, low electrode potential, low cost, non-toxicity and stability, and have been rapidly developed. The carbon negative electrode materials of lithium-ion batteries are mainly natural graphite and artificial graphite. At present, the modification technology of carbon negative electrode materials is mainly through multi-phase coating technology to construct core-shell structure, doping, surface oxidation, etc., so as to improve the electrochemical performance. However, there are still many problems, such as poor contact between electrode material particles and between electrode material particles and current collector, large surface resistance, poor peel strength, cyclic expansion during charge and discharge, etc. The above problems seriously affect the cycle life and stability of lithium-ion batteries.
[0003] The layered structure of graphite materials also determines that lithium ions must first be embedded from the end face of the material and then gradually diffuse into the interior of the particles, which will result in a longer diffusion path, and the smaller interlayer spacing will result in a lower diffusion rate of lithium ions and poorer rate performance. In addition, during fast charging, lithium ions tend to deposit on the graphite surface to form lithium dendrites, which can cause serious safety hazards. Therefore, the orientation of the negative electrode graphite material in the battery should be as perpendicular to the current collector as possible, which is conducive to reducing the resistance to lithium ion embedding and improving the rate charging performance.
[0004] In terms of particle size, it is generally believed that small-particle graphite (about 6μm) has better rate charging performance than large-particle graphite (about 44μm). Although the specific surface area of the material is closely related to the fast charging capability, the larger the specific surface area, the larger the irreversible capacity of the material. In addition, compaction density is also an important reference indicator. Appropriate compaction density can reduce internal resistance and polarization, facilitate the insertion and removal of lithium ions, and take into account both capacity and rate performance.
[0005] In order to improve the fast charging performance of graphite materials, there are currently many methods to dope graphite, such as increasing lithium ion embedding channels, functionalizing the graphite surface, coating the surface with soft and hard carbon, and element doping, etc. However, the above methods have the problem of unsatisfactory embedding effect. Summary of the invention
[0006] The main purpose of the present invention is to provide a fast-charging graphite negative electrode material with multi-metal doping and a preparation method thereof, so as to make the metal doping of graphite more uniform.
[0007] To achieve the above object, the present invention provides a method for preparing a multi-metal doped fast-charging graphite negative electrode material, comprising the steps of:
[0008] S1, doping a graphite material with at least one first metal ion;
[0009] S2, doping the graphite material doped in step S1 with at least one second metal ion to obtain multi-metal doped graphite; wherein the size of the first metal ion is larger than that of the second metal ion;
[0010] S3, heating and reducing the multi-metal-doped fast-charging graphite negative electrode material in a reducing atmosphere to obtain the multi-metal-doped fast-charging graphite negative electrode material.
[0011] Furthermore, the first metal ion in step S1 includes vanadium.
[0012] Furthermore, the method of doping the first metal ion in step S1 includes:
[0013] S11, using magnetron sputtering deposition and physical vapor deposition to deposit vanadium pentoxide on the surface of graphite;
[0014] S12, subjecting the material obtained in step S11 to high-temperature carbonization treatment in a reducing atmosphere, and then crushing it to obtain the graphite material doped in step S1.
[0015] Furthermore, before step S12, the process also includes dispersing the material obtained in step S11 in an organic solvent and then filtering it.
[0016] Furthermore, the graphite material in step S1 is one or more of natural flake graphite, microcrystalline graphite, crystalline vein graphite, artificial graphite, natural spherical graphite, mesophase carbon microspheres, conductive graphite, graphene and graphite fiber.
[0017] Furthermore, the method of doping the second metal ion in step S2 includes:
[0018] S21, soaking the graphite material doped in step S1 with a silver salt solution, wherein the second metal ion includes Ag;
[0019] S22, annealing the material obtained in step S21 in an inert atmosphere, and then reducing it in a hydrogen atmosphere, wherein the reduction temperature of the hydrogen atmosphere matches the decomposition temperature of the silver salt, and then crushing it to obtain graphite doped with multiple metals.
[0020] Furthermore, the silver salt is silver nitrate, and the reduction temperature under the hydrogen atmosphere is 440-460°C.
[0021] Furthermore, the present invention also provides a fast-charging graphite negative electrode material with multi-metal doping, which is prepared by the preparation method as described in any one of the above claims.
[0022] The present invention also provides a negative electrode current collector for a lithium ion battery, the negative electrode current collector comprising: a conductive substrate and a negative electrode slurry layer coated on one or both sides of the conductive substrate, the negative electrode slurry layer being prepared by any of the preparation methods described above.
[0023] The present invention further provides a lithium ion battery, comprising a positive electrode, an electrolyte and a negative electrode, characterized in that the negative electrode comprises the lithium ion battery negative electrode collector as described above.
[0024] In the preparation method of the multi-metal doped fast-charging graphite negative electrode material of the present invention, a first metal ion with a larger size is first doped into the graphite material. The doping of the first metal ion enlarges the interlayer spacing, thereby effectively promoting the subsequent doping of the second metal ions Ag and Au; the doping of Ag and Au effectively improves the conductivity of the material, and is also beneficial to the embedding and precipitation of lithium ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0026] Figure 1 This is the EDS surface scan of the graphite material directly doped with Ag in Example 1.
[0027] Figure 2 This is the EDS surface scan of the graphite material directly doped with V in Example 2.
[0028] Figure 3 Example 1: EDS surface scan of graphite material doped with V and then with Ag. DETAILED DESCRIPTION
[0029] The technical solution in this embodiment will be described clearly and completely below in conjunction with the drawings in this embodiment. Obviously, the described embodiment is only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In addition, the technical solutions between the various embodiments of the present invention can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0031] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0032] Comparative Example 1
[0033] Selection of graphite material: 100g of artificial graphite with a carbon content of more than 85% and a particle size of 3 to 40μm.
[0034] 10 g of Ag powder (commercially available, with a fineness of more than 90 mesh and a purity of 99.99%) is dissolved in 50 ml of an organic solvent (carbon tetrachloride) to form a suspension; the suspension is atomized and then deposited on a graphite material under an inert atmosphere and vacuum conditions.
[0035] In an argon inert atmosphere, the graphite material directly doped with Au and Ag was obtained by carbonization at 900°C for 3h, crushing and acid washing.
[0036] Comparative Example 2
[0037] Selection of graphite material: 100g of artificial graphite with a carbon content of more than 85% and a particle size of 3 to 40μm.
[0038] Vanadium pentoxide is used as the target source, and the magnetron sputtering method is used to deposit the vanadium pentoxide material on the graphite surface. The specific parameter conditions of the magnetron sputtering method are: the reaction chamber is evacuated to 10Pa, the sputtering atmosphere is argon, the sputtering current is 400mA, the sputtering voltage is 800V, the sputtering temperature is 250℃, and the sputtering time is 45min.
[0039] In an argon inert atmosphere, the graphite material directly doped with V was obtained by carbonization at 900°C for 3h and crushing.
[0040] Example 1
[0041] Selection of graphite material: 2g of artificial graphite with a carbon content of more than 85% and a particle size of 3 to 40 μm.
[0042] Vanadium pentoxide was used as the target source, and 10g of vanadium pentoxide material was deposited on the graphite surface by magnetron sputtering. The specific parameter conditions of the magnetron sputtering method were: the reaction chamber was evacuated to 10Pa, the sputtering atmosphere was argon, the sputtering current was 400mA, the sputtering voltage was 800V, the sputtering temperature was 250℃, and the sputtering time was 45min.
[0043] In a hydrogen atmosphere, the graphite material doped with V was obtained by carbonization at 900°C for 3 h and crushing.
[0044] The V-doped graphite material was ultrasonically dispersed in distilled water (60 min), and an immersion solution was prepared according to a mass ratio of silver nitrate to the V-doped graphite material of 0.1:1, and the doped graphite material was immersed for more than 30 min.
[0045] The solid material obtained after filtration was dried and annealed at 100°C in an argon inert atmosphere, and then heated and reduced at 450°C for 2 hours in a hydrogen reducing atmosphere to obtain a fast-charging graphite negative electrode material with multi-metal doping.
[0046] Example 2
[0047] Selection of graphite material: 100g of artificial graphite with a carbon content of more than 85% and a particle size of 3 to 40μm.
[0048] 10 g of vanadium pentoxide is dissolved in 50 ml of an organic solvent (carbon tetrachloride) to form a suspension; in an inert atmosphere and vacuum conditions, the suspension is atomized and then deposited on a graphite material.
[0049] In a hydrogen atmosphere, the graphite material doped with V was obtained by carbonization at 900°C for 3 h and crushing.
[0050] The V-doped graphite material was ultrasonically dispersed in distilled water (60 min), and an immersion solution was prepared according to a mass ratio of silver nitrate to the V-doped graphite material of 0.1:1, and the doped graphite material was immersed for more than 30 min.
[0051] The solid material obtained after filtration was dried and annealed at 100°C in an argon inert atmosphere, and then heated and reduced at 450°C for 2 hours in a hydrogen reducing atmosphere to obtain a fast-charging graphite negative electrode material with multi-metal doping.
[0052] Example 3
[0053] Selection of graphite material: 100g of artificial graphite with a carbon content of more than 85% and a particle size of 3 to 40μm.
[0054] 10 g of vanadium pentoxide, 200 ml of anhydrous ethanol and graphite material were placed in a high-energy ball milling jar, high-energy ball milled at a speed of 1200 rpm for 8 h, and dried in a drying oven at 80 ° C for 24 h to obtain a mixed material;
[0055] In a hydrogen atmosphere, the graphite material doped with V was obtained by carbonization at 900°C for 3 h and crushing.
[0056] The V-doped graphite material was ultrasonically dispersed in distilled water (60 min), and an immersion solution was prepared according to a mass ratio of silver nitrate to the V-doped graphite material of 0.1:1, and the doped graphite material was immersed for more than 30 min.
[0057] The solid material obtained after filtration was dried and annealed at 100°C in an argon inert atmosphere, and then heated and reduced at 450°C for 2 hours in a hydrogen reducing atmosphere to obtain a fast-charging graphite negative electrode material with multi-metal doping.
[0058] Please refer to Figure 1 This is an electron microscope photo of direct Ag doping. It can be seen that Ag is doped on the surface of graphite. Figure 2 From the electron microscope image of V doped alone, we can see that when V is doped, the interlayer spacing of graphite increases significantly. Figure 3 It can be seen that after the incorporation of V expands the interlayer spacing, Ag is doped again, and this time Ag is doped at the position of the interlayer spacing. The incorporation of V expands the interlayer spacing, thereby effectively promoting the incorporation of Ag; the incorporation of Ag effectively improves the conductivity of the material and is also conducive to the embedding and precipitation of lithium ions.
[0059] The electrical performance tests were performed on Comparative Examples 1-2 and Examples 1-3.
[0060] At room temperature, the batteries of the embodiment and the comparative example were subjected to a capacity test: first, they were charged at a constant current of 0.5C to a voltage of 4.5V, and then they were charged at a constant voltage to a current of 0.05C; then, the batteries charged to 4.5V were discharged: they were discharged at a constant current of 0.5C to a voltage of 3.0V.
[0061] At room temperature, the batteries of the embodiment and the comparative example were subjected to a discharge rate performance test: first, they were charged at a constant current of 0.5C to a voltage of 4.5V, and then they were charged at a constant voltage to a current of 0.05C; then the batteries charged to 4.5V were discharged: they were discharged at constant currents of 0.5C and 2C to a voltage of 3.0V, respectively.
[0062] At room temperature, the batteries of the embodiment and comparative example were charged to 4.5V at 1C constant current, then charged to 0.05C at constant voltage, and then discharged to 3.0V at 1C constant current. This charging / discharging process was repeated 500 times.
[0063] The test results are shown in the following table:
[0064] First effect test 2C discharge capacity retention rate Capacity retention after 500 charge / discharge cycles Comparative Example 1 95.1 90.1 77.5% Comparative Example 2 96.3 92.2 69.3% Example 1 99.3 96.7 92.1% Example 2 99.1 96.4 91.4% Example 3 99.1 95.9 90.5%
[0065] Comparative Example 2 introduces V-support to increase the interlayer spacing, and the first efficiency and 2C discharge capacity retention rates are higher than those of Comparative Example 1; however, Comparative Example 1 introduces precious metal doping to improve the conductivity, and the long cycle retention rate of Comparative Example 1 is higher.
[0066] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a fast-charging graphite negative electrode material with multi-metal doping, characterized in that: Includes steps: S1, doping a graphite material with at least one first metal ion; S2, doping the graphite material doped in step S1 with at least one second metal ion to obtain multi-metal doped graphite; wherein the size of the first metal ion is larger than that of the second metal ion; S3, heating and reducing the multi-metal-doped fast-charging graphite negative electrode material in a reducing atmosphere to obtain the multi-metal-doped fast-charging graphite negative electrode material.
2. The method according to claim 1, characterized in that: The first metal ion in step S1 includes vanadium.
3. The method according to claim 2, characterized in that The method of doping the first metal ion in step S1 includes: S11, using magnetron sputtering deposition and physical vapor deposition to deposit vanadium pentoxide on the surface of graphite; S12, subjecting the material obtained in step S11 to high-temperature carbonization treatment in a reducing atmosphere, and then crushing it to obtain the graphite material doped in step S1.
4. The method according to claim 3, characterized in that: Before step S12, the method further includes dispersing the material obtained in step S11 in an organic solvent and then filtering it.
5. The method according to claim 1, characterized in that The graphite material in step S1 is one or more of natural flake graphite, microcrystalline graphite, crystalline vein graphite, artificial graphite, natural spherical graphite, mesophase carbon microspheres, conductive graphite, graphene and graphite fiber.
6. The method according to claim 1, characterized in that The method of doping the second metal ion in step S2 includes: S21, soaking the graphite material doped in step S1 with a second metal salt solution, wherein the second metal ion includes Ag; S22, annealing the material obtained in step S21 in an inert atmosphere, and then reducing it in a hydrogen atmosphere, wherein the reduction temperature of the hydrogen atmosphere matches the decomposition temperature of the silver salt, and then crushing it to obtain graphite doped with multiple metals.
7. The method according to claim 6, characterized in that The second metal salt is silver nitrate, and the reduction temperature under the hydrogen atmosphere is 440-460°C.
8. A fast-charging graphite negative electrode material with multi-metal doping, characterized in that: The method is prepared according to any one of claims 1 to 8.
9. A negative electrode current collector for a lithium ion battery, characterized in that: The negative electrode current collector comprises: a conductive substrate and a negative electrode slurry layer coated on one side or both sides of the conductive substrate, wherein the negative electrode slurry layer is prepared by the preparation method according to any one of claims 1 to 7.
10. A lithium ion battery comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The negative electrode comprises the negative electrode current collector of the lithium ion battery as claimed in claim 9.